Forensic Monitoring Project Report: Gradačac Exhumation and Surface Collections Republika Srpska Commission on Missing Persons - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: York, Heather On 17 July 1998 the Republika Srpska Commission on Missing and Tracing investigated a site near the town of Gradačac. The Commission hoped to find the bodies of six soldiers, but no human remains were encountered at this site. Place of Exhumation: Gradačac Date of Exhumation: 17 July 1998 Minimum Number of Exhumed Individuals: 000